Corporate Social Responsibility in Developing Country Multinationals: Identifying Company and Country-Level Influences - Preuss, Lutz (Business ethics quarterly, 2016)
The extant literature on cross-national differences in approaches to corporate social responsibility (CSR) has mostly focused on developed countries. Instead, we offer two inter-related studies into corporate codes of conduct issued by developing country multinational enterprises (DMNEs). First, we analyse code adoption rates and code content through a mixed methods design. Second, we use multilevel analyses to examine country-level drivers of differences in code content—specifically, elements of a country’s National Business System (NBS). We find that DMNEs are much more likely to adopt a code of conduct than their domestic counterparts; however, this does not translate into greater code comprehensiveness. We also find support for the ‘substitute view’ of CSR in developing countries, i.e. that MNEs from poorer countries and from countries with lower governance effectiveness tend to express more comprehensive commitments. However, this dynamic does not extend to a country’s labour system; instead, CSR appears here to match the efficiency of a country’s labour market, thus reflecting the ‘mirror view’ of CSR.